Microbiological quality of Powdered milk formula sold in Quito, Ecuador - Terán Soto, Rommy I.; Carrión Albán, Kimberly V.; Goetschel Gómez, Lorena (ACI Avances en Ciencias e Ingenierías, 2022)
Human milk is recognized as the best form of nutrition for infants. However, where breast-feeding is not possible, infant milk formulae are used as breast milk substitutes. These formulae provide infants essential nutrients for their normal growth and development, but pathogenic microbes responsible for serious illness could contaminate them. The purpose of this study was to investigate the microbial quality of powdered formulae sold in Quito A total of 12 powdered infant formula and 12 powdered follow-up formula were collected from markets in Quito in 2019. Microbiological quality of samples was analyzed using conventional culture methods. According to the microbiological criteria specified in the Ecuadorian regulation, all powdered infant formulae comply with the total count of aerobic mesophilic organisms and enterobacteria. However, 6 powered follow-up samples do not comply with the regulation. The isolated bacterial genus in the samples were Klebsiella oxytoca (41.7%), Pantoea agglometans, Citrobacter freundii (25%), Bacillus subtilis (16.7%) and Pseudomonas (8.3%). The isolated bacteria genus in follow-up formula were Bacillus subtilis (75%), Bacillus cereus, Klebsiella oxytoca (25%) and Enterobacter aerogenes (25%), Hafnia alvei (16.7%) Escherichia coli (8,3%) and Pantoea agglomerans in the 8.3% of the samples. Salmonella was not found in any sample. This study indicates the necessity of conducing further microbial contamination research in powdered formula products because they could be a potential source of food contaminants and a risk for infants and babies.